Annotated bird sighting list for Fall 1980 submitted by Robert K. Myers - Myers, Robert K.et al (1980)
Robert K. Myers provides an annotated list of birds sighted by himself and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1980. Epson - sheet feed/flatbed